Metadata Management in the Digital Age: A Qualitative Approach to Practices and Challenges in Modern Organizations - Silvia Meiliandari; Muhammad Irwan Padli Nasution; Hairul Anam (ISNU Sumatera Utara, 2025)
In the era of massive digital transformation, organizations across various sectors face significant challenges in managing increasingly complex and growing volumes of data. Metadata, as descriptive information about data, plays a central role in ensuring that data can be found, understood, and reused appropriately. Metadata management not only assists in managing digital archives but also serves as the foundation for effective and efficient data governance. This study aims to explore metadata management practices in five modern organizations from the government, private sector, and nongovernmental organizations. Using a qualitative approach with in-depth interviews, system observations, and documentation studies, this study identifies the extent of metadata understanding, implementation, and challenges in real-world work environments. The results indicate that most organizations still face gaps in standardization, system interoperability, and human resource digital literacy. This study also suggests the need for a national metadata strategy and ongoing training to encourage optimal metadata utilization across all organizational levels.